2018
DOI: 10.1587/transinf.2017dar0001
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Thai Knowledge Extraction for the Semantic Web Research and Tools

Abstract: As the manual creation of domain models and also of linked data is very costly, the extraction of knowledge from structured and unstructured data has been one of the central research areas in the Semantic Web field in the last two decades. Here, we look specifically at the extraction of formalized knowledge from natural language text, which is the most abundant source of human knowledge available. There are many tools on hand for information and knowledge extraction for English natural language, for written Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Especially, analyzing Thai texts is made difficult by features. The Thai language is complex because it includes adjustable word order, serial verbs, and high incertitude in compound words [14]. It requires a high-performance word segmentation as it has no word boundary indicators to separate words in sentences.…”
Section: Text Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, analyzing Thai texts is made difficult by features. The Thai language is complex because it includes adjustable word order, serial verbs, and high incertitude in compound words [14]. It requires a high-performance word segmentation as it has no word boundary indicators to separate words in sentences.…”
Section: Text Preprocessingmentioning
confidence: 99%
“…The Thai sentences rely on individual judgment when there are unknown words, while English sentences have natural spaces. Besides, Thai has structural ambiguities in which Part-of-Speech (POS) tags relied on context words that affect one word may have the opposite meaning [8,14,15,16,17]. Thus, data preprocessing has involved the analysis of Thai sentences.…”
Section: Text Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the previous evaluations reported a number of difficulties with the pretrained models, first of all, a high number of out-of-vocabulary (OOV) terms [ 18 ]. The problem is related to the peculiarities of Thai language, which were discussed at length in Netisopakul and Wohlgenannt [ 20 ]. In brief, firstly, written Thai language, like some other Asian languages (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Compound vowels can be constructed in various ways by combining vowel characters and consonants, and be placed above, below, before or after the consonants. Further complications in Thai NLP include zero anaphora, the absence of upper/lower-case characters, high ambiguity of compound words, and serial verbs [12]. In contrast to English, Thai is a tonal language with five different tones, making it a very difficult language for English native speakers to comprehend.…”
Section: Introductionmentioning
confidence: 99%